2009
DOI: 10.1002/ase.105
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative changes in teaching histology by means of virtual microscopy in an introductory course in human anatomy

Abstract: This study compares overall laboratory averages and individual test scores along with a student survey to determine the effects of using virtual microscopy in place of optical microscopes in a large undergraduate human anatomy course. T-tests revealed that the first two laboratory examinations (of four) and the overall laboratory averages were significantly increased compared with the previous year. We hypothesize that this is due to students' ability to use and understand the technology quickly as opposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 18 publications
5
81
1
1
Order By: Relevance
“…Although free Internet atlases of static histological images are important in terms of becoming familiar with the concept of microscopic anatomy, to teach histology/histopathology, interactive cloud-based "Webmicroscope" servers started to be used only 5-10 years ago (Brisbourne et al 202;Lundin et al 2004;Scoville et al 2007;Pinder et al 2008;Husmann et al 2009;Dee 2009;Gona et al 2012;Sung et al 2015). Following this international trend in histology education, we changed our classical, static-glass-slide-based and teacher-focused style of sharing information in 2016 to a new IT-and cloud-based system using WEBMICROSCOPE ® software combined with studentfocused teaching methods.…”
Section: Discussionmentioning
confidence: 99%
“…Although free Internet atlases of static histological images are important in terms of becoming familiar with the concept of microscopic anatomy, to teach histology/histopathology, interactive cloud-based "Webmicroscope" servers started to be used only 5-10 years ago (Brisbourne et al 202;Lundin et al 2004;Scoville et al 2007;Pinder et al 2008;Husmann et al 2009;Dee 2009;Gona et al 2012;Sung et al 2015). Following this international trend in histology education, we changed our classical, static-glass-slide-based and teacher-focused style of sharing information in 2016 to a new IT-and cloud-based system using WEBMICROSCOPE ® software combined with studentfocused teaching methods.…”
Section: Discussionmentioning
confidence: 99%
“…Multimedia has gained substantial user approval in providing opportunities to study microscopic anatomy consisting of histology and pathology (in relation to genetics) through virtual microscopy (Durosaro et al, 2008;Husmann et al, 2009) and a vast library of web-based multimedia animations (Downing, 1995;Brisbourne et al, 2002). Yet, the inclusion of microscopic anatomy depends on the institution and may not necessarily exist within the teaching block of anatomy.…”
Section: Interactive Multimediamentioning
confidence: 99%
“…A t-test analysis showed that the first two laboratory exams and the overall lab averages were significantly increased compared to years relying on optical microscopes. Students showed a preference to the electronic resources and lecture videos in the survey pointing out that increased access, ease of use, and their increased chances to understand the material made them choose virtual microscope teaching [18]. These studies come to prove that crossing paths and integrating different aspects of medical education is more efficacious in terms of students' commitments, interest, and scores.…”
Section: Histology In the New Curriculummentioning
confidence: 94%